2001
DOI: 10.1002/xrs.472
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of detection efficiency and response functions for an Si(Li) x‐ray spectrometer in the range 0.1–5 keV

Abstract: Efficiency and response functions were determined for a modern commercial energy-dispersive x-ray spectrometer in the photon energy range 0.1-5 keV using dispersed and undispersed synchrotron radiation. The spectrometer was equipped with an Si(Li) detector crystal, a thin-film window and a digital pulse processor. Monochromatized synchrotron radiation from the PTB VUV radiometry beamline at the electron storage ring BESSY was used for the absolute determination of the detection efficiency with a typical relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 23 publications
3
81
0
Order By: Relevance
“…With monochromatic synchrotron radiation response functions could be measured for all photon energies of interest between 0.1 keV and several tens of keV. [6,10] Owing to the long calculation times needed and the statistical nature of the results, Monte Carlo simulations are not the way to go for practical applications where smooth response functions for large numbers of photon energies are needed to convolute calculated photon spectra for comparison with measured MCA pulse height spectra.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With monochromatic synchrotron radiation response functions could be measured for all photon energies of interest between 0.1 keV and several tens of keV. [6,10] Owing to the long calculation times needed and the statistical nature of the results, Monte Carlo simulations are not the way to go for practical applications where smooth response functions for large numbers of photon energies are needed to convolute calculated photon spectra for comparison with measured MCA pulse height spectra.…”
Section: Discussionmentioning
confidence: 99%
“…However, a also determines the depth z 0 where C approaches unity and is thus given by the total number of counts in the tail, see Eqn (3). In a previous article [10] we used a sum of two exponential functions; effectively, the first was used to adjust the slope at z = 0 and the second to adjust z 0 . In order to keep the number of free parameters as small as possible, the function…”
Section: Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Our message differs from all previous investigators, as we declare that the signal processor DOES modify the spectra as confirmed by experiments. We recommend the reader look at the spectra presented in the literature [19][20][21][22][24][25][26] to see the large variations.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the response functions are well understood and simulations, frequently based on Monte Carlo methods, reproduce well all the spectral features whatever the incident energy 4, 5,6,7,8 . Below a few keV, the low energy tail accompanying the full absorption energy peak is known to be mainly due to incomplete charge collection effects 5,6,7 that occur at low incident photon energies. For much higher incident photon energies (above a few tens of keV), a small fraction of photons interacts with the quasi-free electrons of the detector material and is scattered, losing part of their energy in the detector or escaping from the detector.…”
Section: Introductionmentioning
confidence: 99%